Properties of 15Cr12WNiMoV steel after vacuum activated chromium plating of its surface - Rudenky, S.G.; Kartzev, N.F.; Korneev, A.A.; Kunchenko, A.V.; Kunchenko, Y.V.; Marinin, V.G.; Martynenko, L.I.; Kovalenko, V.I.; Bortnytska, M.O.; Ryzhova, T.P.; Lashenko, I.A.; Gozhenko, S.V.; et al. (Вопросы атомной науки и техники, 2021)
In this work, we studied the properties of samples from steel 15Cr12WNiMoV after vacuum activated chromium plating at temperatures of 1070 and 1100 °C for 4 and 10 h. It was found that after chemical-thermal treatment on the samples a diffusion layer with a thickness of 50 to 130 µm is formed, consisting of 56…82 wt.% of chromium, the rest is iron. Metallographic studies were carried out on the samples and tests for heat resistance were carried out at a temperature of T = 900 °C. It was found that chrome-plated samples significantly exceed the initial samples and nitrided ones in terms of heat resistance. Tests of samples for tensile strength after chromium plating showed a significant increase in strength indicators for ultimate strength and yield strength. The plasticity characteristics of these samples are reduced. Проведені дослідження властивостей зразків зі сталі 15Х12ВНМФ після вакуумного активованого хромування при температурах 1070 і 1100 °С протягом 4 і 10 год. Установлено, що після хіміко-термічної обробки на зразках формується дифузійний шар товщиною від 50 до 130 мкм, що складається з 56…82 ваг.% хрому, інше – залізо. На зразках були проведені металографічні дослідження й здійснені випробування на жаростійкість при Т = 900 °С. Установлено, що хромовані зразки по жаростійкості значно перевершують вихідні зразки й азотовані. Проведені випробування зразків на міцність на розрив після хромування показали істотне збільшення міцностних показників для межі міцності й межі текучості. Характеристики пластичності цих зразків зменшуються. Проведены исследования свойств образцов из стали 15Х12ВНМФ после вакуумного активированного хромирования при температурах 1070 и 1100 °С в течение 4 и 10 ч. Установлено, что после химикотермической обработки на образцах формируется диффузионный слой толщиной от 50 до 130 мкм, состоящий из 56…82 вес.% хрома, остальное – железо. На образцах были проведены металлографические исследования и осуществлены испытания на жаростойкость при Т = 900 °С. Установлено, что хромированные образцы по жаростойкости значительно превосходят исходные образцы и азотированные. Проведенные испытания образцов на прочность на разрыв после хромирования показали существенное увеличение прочностных показателей для предела прочности и предела текучести. Характеристики пластичности этих образцов уменьшаются.